Framework Agreement between the Government of Iceland and the Government of the People's Republic of China on Arctic Cooperation (Government of Iceland, 2012)
The Government of the People's Republic of China and the Government of Iceland (hereinafter referred to as "the Parties"), Reaffirming the friendly bilateral relations between the countries, Recognizing that cooperation between Arctic States and non-Arctic States can promote studies of trans-regional Arctic issues, Desiring to cooperate on Arctic issues, on the basis of mutual respect, reciprocity and mutual benefit, with the aim to further strengthen their friendly bilateral relations